Case report: A rare case of Rosai–Dorfman–Destombes disease after the COVID-19 infection - Gogia, Pooja; Tanni, Fahmina; Coca-Guzman, Juan; Chen, Neil; Huang, Yiwu (Frontiers in Medicine, 2022)
Coronavirus disease 2019 (COVID-19) caused by the severe acute respiratory syndrome coronavirus 2, or SARS-CoV-2 is known to cause immune dysregulation and hence has varied and often rare presentations. Rosai-Dorfman-Destombes disease is an unusual non-Langerhans cell histiocytosis presenting with massive lymphadenopathy and diverse systemic symptoms. A 55-year-old Asian American female with no significant past medical history or recent new drug use initially presented with cervical lymphadenopathy and urticarial rash a week after receiving messenger RNA vaccination (Moderna, mRNA-1273) against SARS-CoV-2. The biopsy of the rash was consistent with drug reaction. Around two months later, developed mild flu like symptoms and was diagnosed with COVID-19 infection. Her symptoms were mild and self-resolved. Three months later, she developed generalized patchy erythematous body rash worse on the face, diffuse lymphadenopathy involving bilateral cervical, axillary and inguinal area and constitutional symptoms. Labs consistent with lymphopenia, anemia and elevated sedimentation rate. Supraclavicular lymph node biopsy showed Rosai-Dorfman disease with marked polyclonal plasma cytosis. She was started on tapering dose of corticosteroids and showed clinical improvement over the next few weeks. Herein, we present a rare entity of histiocytic disorder manifesting after receiving mRNA vaccine and further after contracting the SARS-COV2 infection.